Seasonal Variations in Antibiotic Resistance Gene Transport in the Almendares River, Havana, Cuba - Knapp, Charles W.; Lima, Lazaro; Olivares-Rieumont, Susana; Bowen, Emma; Werner, David; Graham, David W (Frontiers in Microbiology, 2012)
Numerous studies have quantified antibiotic resistance genes (ARG) in rivers and streams around the world, and significant relationships have been shown that relate different pollutant outputs and increased local ARG levels. However, most studies have not considered ambient flow conditions, which can vary dramatically especially in tropical countries. Here, ARG were quantified in water column and sediment samples during the dry- and wet-seasons to assess how seasonal and other factors influence ARG transport down the Almendares River (Havana, Cuba). Eight locations were sampled and stream flow estimated during both seasons; qPCR was used to quantify four tetracycline, two erythromycin, and three beta-lactam resistance genes. ARG concentrations were higher in wet-season versus dry-season samples, which combined with higher flows, indicated much greater ARG transport downstream during the wet-season. However, water column ARG levels were more spatially variable in the dry-season than the wet-season, with the proximity of waste outfalls strongly influencing local ARG levels. Results confirm that dry-season sampling provides a useful picture of the impact of individual waste inputs on local stream ARG levels, whereas the majority of ARGs in this tropical river were transported downstream during the wet-season, possibly due to re-entrainment of ARG from sediments.